A method for journal collection management and the limitations of reality - Lorenz, Miriam (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
Academic libraries are constantly facing new challenges, which require as much time and money as other processes to be more effective. A big part of the media budget is spent on licensing (electronic) journals. Even though libraries invest a lot of time in selection processes of journals, it is still not possible to combine the data (like statistics or JIF) of the different actors of scholarly communication in a multidimensional model and to produce a balanced base for decision making. This work shows the requirements of such a model and explains, which deficits exist at present and why the Data Envelopment Analysis (DEA) is a suitable method for the selection process of (e)journals.